Implementasi Penyusunan Laporan Keuangan Sesuai PSAK-EMKM Pada IKM GAZAL MAKMUR Kabupaten Probolinggo - Dyah Ayu Perwitasari; Novita Lidiyana; Trivosa Aprilia Novadiani Haidiputri (Fakultas Ekonomi Universitas Panca Marga, 2022)
This research was conducted at IKM GAZAL MAKMUR, Probolinggo Regency. The purpose of this study is to make it easier for owners to prepare financial statements in accordance with financial accounting standards (SAK-EMKM). The type of research used is a qualitative case study approach. The data was taken by using the interview method, and documentation. The problem that occurs in IKM GAZAL MAKMUR is that financial records have been carried out using a simple method. The recording of cash in and cash out is considered to represent the entirety of the financial records carried out. This means that the application is not in accordance with the applicable SAK-EMKM. The limited capacity of human resources in preparing financial reports, which are not in accordance with SAK EMKM, is the main problem from the results of the research conducted. So for going concern business and financial transparency, financial records must be recorded, in accordance with the guidelines in the applicable standards. Keyword: UMKM, Financial Reports, SAK EMKM